Dual-band Circularly-polarized Millimeter-wave Substrate Integrated Waveguide Slot Antenna Array with a Small Frequency Ratio - Li, Jianxing; Yu, Xiaoyan; Wu, Sifan; Yan, Sen; Xu, Kai-Da (Applied Computational Electromagnetics Society Journal (ACES), 2024)
In this paper, a 4×4 dual-band circularly-polarized (CP) substrate integrated waveguide (SIW) slot antenna array with a small frequency ratio (FR) is investigated in the Ka-band. The proposed antenna array achieves the small FR by radiating two high-order modes, i.e. TM130 and TM230, with close resonant frequencies. To realize CP performance, a sequential rotated feeding (SRF) network is used to design a 2×2 subarray. A 4×4 CP antenna array is further developed to enhance the directivity. Measured results show the antenna array achieves impedance bandwidth (|S11| < -10 dB) of 27.35-27.96 GHz at the lower band and 29.62-30.58 GHz at the higher band with an FR of only 1.1. The measured 3-dB axial-ratio (AR) bandwidths are obtained as 27.66-27.78 GHz and 30.34-30.45 GHz with right-handed circularly-polarized (RHCP) peak gains of 16.9 and 16.8 dBi, respectively. The proposed antenna array is a potential candidate for millimeter-wave communication systems.